Evaluating the Impact of Promotional Tools on Consumer Behaviour: Insights from Haryana Tourism Corporation - Kumari, Meenu; Dutt, Amit; Kaur, Jaskiran (Journal of Neonatal Surgery, 2025)
Background: Promotional tools play a crucial role in shaping consumer behavior, particularly in the tourism sector, where competition is intense, and customer preferences evolve rapidly. This study investigates the impact of various promotional tools utilized by Haryana Tourism Corporation, focusing on identifying the most effective strategies for influencing customer decisions. By examining promotional tools such as advertisements, referral programs, discounts, and social media campaigns, this research provides actionable insights for enhancing customer engagement and satisfaction. Methodology: The study adopts a mixed-methods approach, employing SPSS for descriptive, correlation, and regression analysis, complemented by SmartPLS for structural modeling. A survey was conducted among 163 respondents, using a structured questionnaire to evaluate their perceptions of different promotional tools. Statistical techniques such as ANOVA and path analysis were used to determine the effectiveness and interrelationships of the promotional strategies. Findings: The results reveal that advertisements, referral programs, and discounts are the most impactful promotional tools, with referral programs having the highest influence on customer behavior. Social media campaigns, although less effective in SPSS analysis, gained prominence in SmartPLS due to their latent potential. Regression analysis indicated that promotional tools collectively explain 52.5% of the variance in customer behavior, with referral programs exhibiting the strongest correlation and influence. The findings underscore the importance of integrating referral strategies with personalized email campaigns for enhanced impact. Implications: The study highlights the need for a strategic, multi-channel approach to promotional activities in tourism. Haryana Tourism Corporation can leverage the insights to optimize its promotional strategies, aligning them with customer preferences and emerging trends. Enhancing social media campaigns and refining email marketing are critical to maximizing their latent potential and improving overall effectiveness.